2020
DOI: 10.26686/wgtn.13058594.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cost benefit analysis of an active travel intervention with health and carbon emission reduction benefits

Abstract: © 2018 by the authors. Licensee MDPI, Basel, Switzerland. Active travel (walking and cycling) is beneficial for people’s health and has many co-benefits, such as reducing motor vehicle congestion and pollution in urban areas. There have been few robust evaluations of active travel, and very few studies have valued health and emissions outcomes. The ACTIVE before-and-after quasi-experimental study estimated the net benefits of health and other outcomes from New Zealand’s Model Communities Programme using an emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Gu, et al [ 50 ] found that investments in cycle lanes are more cost-effective than the majority of preventive approaches used nowadays. Other studies have also reported positive benefit-cost ratios [ 1 , 12 , 51 ]. Recently, there has been a growing need for health economic evaluations of such programs because they assist decision-makers in establishing priorities within cost-constrained health care budgets.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Gu, et al [ 50 ] found that investments in cycle lanes are more cost-effective than the majority of preventive approaches used nowadays. Other studies have also reported positive benefit-cost ratios [ 1 , 12 , 51 ]. Recently, there has been a growing need for health economic evaluations of such programs because they assist decision-makers in establishing priorities within cost-constrained health care budgets.…”
Section: Discussionmentioning
confidence: 96%
“…Studies suggest that cycle-network investments can increase cycling [ 1 3 ] and thereby improve health at the population level [ 4 , 5 ]. The national and local governmental authorities in Norway have aimed to support the growth of cycling as a means of transportation with the aim to improve health through increased physical activity.…”
Section: Introductionmentioning
confidence: 99%